(untitled) (Bangladesh Journal of Medical Science, 2025)
Background & Aims Many adolescent girls and young women experience painful periods, medically known as primary dysmenorrhea (PD). Vitamin D deficiency and high cortisol levels seem to be connected and may even worsen the symptoms of PD. The aim of this research was to determine possible relationship between vitamin D and salivary cortisol levels in adolescent girls with PD. Methodology A total of 191 adolescent girls with PD aged 13-16 years were examined. All participants were randomly divided into two groups: the main group (n =96), which took vitamin D 4000 IU per day for three months and the control group (n =95), which took placebo. Further laboratory tests were carried out to determine the level of 25(OH) vitamin D in the blood serum and 4 samples of saliva to evaluate cortisol levels during the day before and after the intervention. Results & Conclusion After the intervention in the main group, an average negative relationship was revealed between the content of 25(OH) vitamin D in the blood with morning (r=- 0.4, p=0.001) and daytime (r=-0.25, p=0.041) levels of cortisol in the saliva of adolescent girls with PD, while no significant relationships were identified in the control group. We found that higher vitamin D levels were linked to lower cortisol levels in their saliva, especially in the mornings. This suggests a potential benefit of vitamin D in reducing stress hormones in these girls. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 496-504